Associations between sleep disturbances and diabetes mellitus among blacks with metabolic syndrome: Results from the Metabolic Syndrome Outcome Study (MetSO). (May 2015) - Ramos, Alberto R.; Wallace, Douglas M.; Pandi-Perumal, Seithikurippu Ratnas; Williams, Natasha J.; Castor, Chimene; Sevick, Mary Ann; Mcfarlane, Samy I.; Jean-Louis, Girardin
Abstract: Introduction. The association between sleep disturbances and cardiometabolic diseases has been understudied in blacks with metabolic syndrome. Methods. This study is a cross-sectional analysis of the Metabolic Syndrome Outcome Study (MetSO) trial. We assessed insomnia symptoms, sleep duration, and risk for sleep apnea. Multivariate logistic regression models evaluated the association between sleep disturbances with diabetes mellitus (DM) and the combined outcomes of DM and hypertension as well as DM and dyslipidemia. Results. The sample consisted of 1, 013 participants, mean age of 62 ± 14 years and 61% female. DM was diagnosed in 60% of the sample. Sleep apnea risk was observed in 48% of the sample, while 10% had insomnia symptoms and 65% reported short sleep duration (< 6 hours). Sleep apnea risk, but not insomnia or sleep duration, was associated with DM (OR 1.66; 95% CI 1.21–2.28), adjusting for age, sex, income, obesity (BMI ≥ 30 kg/m 2 ), tobacco use, alcohol use, hypertension, dyslipidemia, and depression. In fully adjusted models, sleep apnea risk was associated with the combined outcome of DM–hypertension (OR 1.95; 95% CI 1.42–2.69), but not with diabetes–dyslipidemia. Conclusion. We observed a strong association between sleep apnea risk and diabetes mellitus among blacks with metabolic syndrome.